2002
DOI: 10.1104/pp.128.2.482
|View full text |Cite
|
Sign up to set email alerts
|

Resistance against Herbicide Isoxaben and Cellulose Deficiency Caused by Distinct Mutations in Same Cellulose Synthase Isoform CESA6

Abstract: Isoxaben is a pre-emergence herbicide that inhibits cellulose biosynthesis in higher plants. Two loci identified by isoxabenresistant mutants (ixr1-1, ixr1-2, and ixr2-1) in Arabidopsis have been reported previously. IXR1 was recently shown to encode the cellulose synthase catalytic subunit CESA3 (W.-R. Scheible, R. Eshed, T. Richmond, D. Delmer, and C. Somerville [2001] Proc Natl Acad Sci USA 98: 10079-10084). Here, we report on the cloning of IXR2, and show that it encodes another cellulose synthase isoform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
118
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(128 citation statements)
references
References 13 publications
10
118
0
Order By: Relevance
“…In longitudinally expanding cells, the cellulose microfibrils are deposited primarily in an orientation perpendicular to the axis of expansion, thus constricting radial expansion (Green, 1980;Taiz, 1984;Baskin, 2005). Consistent with this, disruption of cellulose biosynthesis by treatment with various chemical inhibitors results in a rapid loss of growth anisotropy (Scheible et al, 2001;Desprez et al, 2002).…”
Section: Introductionmentioning
confidence: 72%
“…In longitudinally expanding cells, the cellulose microfibrils are deposited primarily in an orientation perpendicular to the axis of expansion, thus constricting radial expansion (Green, 1980;Taiz, 1984;Baskin, 2005). Consistent with this, disruption of cellulose biosynthesis by treatment with various chemical inhibitors results in a rapid loss of growth anisotropy (Scheible et al, 2001;Desprez et al, 2002).…”
Section: Introductionmentioning
confidence: 72%
“…These families tend to be large. For example, the ␣-expansins consist of 26 family members (Lee et al, 2001) and the cellulose synthase family is represented by at least 10 CesA-type genes and 41 Csl (cellulose synthase-like) genes (Richmond and Somerville, 2000;Carpita et al, 2001;Desprez et al, 2002). Here, we report that COBRA is part of a new multigene family with the identification of 11 new family members.…”
mentioning
confidence: 79%
“…Because all other reported CesA mutants with defects in cellulose synthesis are recessive except two herbicide-resistant CesA mutants showing semidominant resistance to herbicides (Scheible et al, 2001;Desprez et al, 2002), it was intriguing to find that the fra5 mutation results in a semidominant effect on cellulose biosynthesis. There are at least two possibilities to explain the semidominant phenotype of the fra5 mutant.…”
Section: Overexpression Of the Fra5 Mutant Cdna Causes Dramatic Reducmentioning
confidence: 99%
“…Since then, several additional Arabidopsis mutants with mutations in CesA genes have been isolated. It has been shown that at least four CesA genes, namely AtCesA1 (RSW1), AtCesA2, AtCesA3 (IXR1/CEV1), and AtCesA6 (PRC1/IXR2), are involved in primary wall synthesis, and mutations or antisense repression of these genes cause a reduction in cellulose synthesis (Arioli et al, 1998;Fagard et al, 2000;Scheible et al, 2001;Burn et al, 2002;Desprez et al, 2002;Ellis et al, 2002). The reduced cellulose synthesis in primary walls is associated with a decrease in cell elongation, which was shown in some of these mutants to be correlated with an increased production of jasmonate and ethylene (Ellis et al, 2002 Article, publication date, and citation information can be found at www.plantphysiol.org/cgi…”
mentioning
confidence: 99%
See 1 more Smart Citation